TATA KELOLA KEUANGAN NAGARI DAN IMPLIKASINYA TERHADAP PEMBANGUNAN NAGARI DI KECAMATAN X KOTO DIATAS KABUPATEN SOLOK - Teta Midra; Asdi Agustar; Ira Wahyuni Syarfi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
Nagari financial governance is a condition implemented by the nagari, starting from budget planning, budget implementation / use, reporting administration and accountability in accordance with statutory regulations. Nagari financial governance must contain the principles of transparency, accountability, participatory, orderly and budgetary discipline so that implementation can run well so as to provide progress in village development. This research aims to determine the composition (posture) and governance of village finances, issues experienced by the nagari in implementing nagari financial management and the implications of nagari finance for village development. This research focuses on Nagari Financial Governance and Its Implications for Nagari Development in X Koto Diatas District, Solok Regency. Data collection techniques for primary data collection were carried out in-depth interviews with key informants in the village. The key informants were the Nagari Wali, Nagari Secretary, Section Head, Head and Head of the Nagari Consultative Body, while secondary data was collected using the documentation method. This research was conducted using a case study method with two villages used as a case (multiple cases), namely Nagari Pasilihan and Nagari Sulit Air. The results of this study indicate that the nagari financial governance is quite good, seen from how the nagari places the composition (posture) in both the revenue and expenditure of the village. The problems of each stage of financial management can be overcome by Nagari from time to time by increasing the competence and capability of the financial management officers. The implications of good nagari financial management are positively proportional to the social, economic and infrastructure aspects of the nagari. Keywords: Nagari Finance, Nagari Financial Governance, Implications, Nagari Development